2018
DOI: 10.1097/qad.0000000000001766
|View full text |Cite
|
Sign up to set email alerts
|

In what circumstances could nondaily preexposure prophylaxis for HIV substantially reduce program costs?

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Because of the recommendations for both daily and on-demand PrEP for MSM, four trials were conducted in developed countries to determine preferences for one regimen over the other and the underlying factors among MSM [8][9][10]; this was particularly important because daily and on-demand regimens differ in terms of pill burden, adherence and cost-effectiveness [11][12][13]. Studies in Belgium, Australia and the Netherlands reported that 66% to 76.5% of MSM preferred daily PrEP, whereas in France, where on-demand PrEP has been recommended since 2015, around 60% of MSM chose on-demand PrEP in the first year of the trial [14].…”
mentioning
confidence: 99%
“…Because of the recommendations for both daily and on-demand PrEP for MSM, four trials were conducted in developed countries to determine preferences for one regimen over the other and the underlying factors among MSM [8][9][10]; this was particularly important because daily and on-demand regimens differ in terms of pill burden, adherence and cost-effectiveness [11][12][13]. Studies in Belgium, Australia and the Netherlands reported that 66% to 76.5% of MSM preferred daily PrEP, whereas in France, where on-demand PrEP has been recommended since 2015, around 60% of MSM chose on-demand PrEP in the first year of the trial [14].…”
mentioning
confidence: 99%
“…As indicated before, being able to safely use PrEP when it is needed may be of paramount importance, rather than focusing on rigidly following a particular dosing regimen for indefinite period of time. Consistent high adherence during periods of non‐exposure is costly . Therefore, Haberer et al called for a novel paradigm: prevention‐effective adherence that proposes the use of PrEP only during periods of heightened risk exposure resulting into effective protection against HIV acquisition .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to anti‐retroviral treatment which need lifelong sustained adherence by people living with HIV, PrEP can be taken temporarily during episodes of anticipated increased risk . Non‐daily regimens also have the advantage of requiring fewer tablets, thus reducing potential side‐effects and cost . However, adherence to these regimens should be optimal, as they are less forgiving of missed doses .…”
Section: Introductionmentioning
confidence: 99%
“…Despite budgetary constraints, PrEP programs in resource limited settings like Côte d'Ivoire should consider offering it free of charge to MSM. In this respect and to reduce the overall economic burden for countries, PrEP programs could promote PrEP, where possible, to men at higher risk like those who have frequent unprotected sex, high number of sexual partners and HIVpositive sexual partners (Beyrer et al, 2012;Buchbinder et al, 2014;Mitchell et al, 2018). In Côte d'Ivoire, PrEP could be available free of charge for MSM in 2020.…”
Section: Discussionmentioning
confidence: 99%